A Noniterative Algorithm for the Multiproduct Production and Work Force Planning Problem - Singhal, Kalyan (Operations research, 1992)
Discrete optimal control theory is used to develop an efficient noniterative algorithm for solving the multiproduct production and work force planning problems with a quadratic cost function. The quadratic cost models allow uncertainties to be handled directly because they minimize the expected cost if unbiased expected demand forecasts are given. A real-world problem may involve as many as 200,000 variables. The noniterative algorithm makes the computations, irrespective of the number of products, not only feasible but also extremely easy and efficient.